Economic Evaluation on the Production of Chitosan-Kaolinite Nanocomposite from Prawn Shell Waste - asep bayu (Indonesian Journal of Digital Business, 2021)
Chitosan-kaolinite clay nanocomposite is one of the nanocomposite biopolymers that can be used to remove heavy metals in wastewater treatment processes. This type of adsorbent can be modified from marine animal waste (especially shells), for example, prawn. The purpose of this study is to analyze if this adsorbent manufacturing project can be carried out or not, by taking into various perspectives including engineering and economic perspectives. Several parameters for economic evaluation have been analyzed in this paper, such as the length of time to obtain initial capital after the project is executed (PBP), the calculation of the total net profit value since the start of construction in years (CNPV), and so on. The results show that this project is prospective from an engineering and economic point of view. Characterized by the capital that is recovered after three years of the project. Marked by the increase in the Profitability Index (PI) value of 86.4230 from -0.9746 which is the second year PI value. In one day this project can produce 37.5 tons from three shifts of work. The total profit earned in one year reached 5,551,803.98 USD under ideal conditions. This project is considered to be able to compete in the market because PBP occurs in the third year of the project. Apart from the results of this economic analysis, this project is considered as a project that can be chosen as a way to utilize aquatic waste as an effort to maintain the beauty of the earth.Chitosan-kaolinite clay nanocomposite is one of the nanocomposite biopolymers that can be used to remove heavy metals in wastewater treatment processes. This type of adsorbent can be modified from marine animal waste (especially shells), for example, prawn. The purpose of this study is to analyze if this adsorbent manufacturing project can be carried out or not, by taking into various perspectives including engineering and economic perspectives. Several parameters for economic evaluation have been analyzed in this paper, such as the length of time to obtain initial capital after the project is executed (PBP), the calculation of the total net profit value since the start of construction in years (CNPV), and so on. The results show that this project is prospective from an engineering and economic point of view. Characterized by the capital that is recovered after three years of the project. Marked by the increase in the Profitability Index (PI) value of 86.4230 from -0.9746 which is the second year PI value. In one day this project can produce 37.5 tons from three shifts of work. The total profit earned in one year reached 5,551,803.98 USD under ideal conditions. This project is considered to be able to compete in the market because PBP occurs in the third year of the project. Apart from the results of this economic analysis, this project is considered as a project that can be chosen as a way to utilize aquatic waste as an effort to maintain the beauty of the earth.